Effect of the glycemic index of pre-exercise snack bars on substrate utilization during subsequent exercise. (12th August 2013) - Sun, Feng-Hua; O'Reilly, John; Li, Liang; Wong, Stephen Heung-Sang
Abstract: Purpose : To investigate the effect of the glycemic index (GI) of pre-exercise snack bars on substrate utilization during subsequent moderate intensity exercise. Methods : Fourteen male participants (Age: 27 ± 5 yr; BMI: 22.5 ± 2.7 kg m −2 ; opagenumbers VO_2 : 48.7 ± 6.1 mL kg −1 min −1 ) completed two trials in a randomized and counterbalanced crossover design. Two iso-caloric snack bars with different GI values (20, LGI versus 68, HGI) were provided to the participants. Ninety minutes later, all participants completed 45 minutes of ergometer cycling at 65% opagenumbers VO_2 . Substrate utilization was measured using indirect calorimetry. Results : During exercise, higher fat oxidation and lower carbohydrate (CHO) oxidation were observed in the LGI trial (LGI versus HGI: CHO, 87.3 ± 20.1 versus 99.2 ± 19.0 g, p < 0.05; Fat, 15.0 ± 5.8 versus 9.7 ± 7.0 g, p < 0.05). Conclusion : Compared with an iso-caloric HGI snack bar, pre-exercise LGI snack bar consumption may facilitate a shift of substrate utilization from CHO to fat during subsequent moderate intensity exercise.